1998
DOI: 10.1038/32891
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory discrimination based on cortical microstimulation

Abstract: The sensation of flutter is produced when mechanical vibrations in the range of 5-50Hz are applied to the skin. A flutter stimulus activates neurons in the primary somatosensory cortex (S1) that somatotopically map to the site of stimulation. A subset of these neurons-those with quickly adapting properties, associated with Meissner's corpuscles-are strongly entrained by periodic flutter vibrations, firing with a probability that oscillates at the input frequency. Hence, quickly adapting neurons provide a dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
394
10
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(433 citation statements)
references
References 15 publications
24
394
10
5
Order By: Relevance
“…Moreover, rabbits acquiring an associative learning using a trace-conditioning paradigm are unable to differentiate between the peripheral or central presentation of the same CS, i.e., their subjective experience was similar for both stimuli (1). These results also suggest that a similar sensory percept is evoked when animals are stimulated in the S1 area for vibrissae as when stimulated directly on the whisker pad (4,5). In this regard, it has been convincingly shown that neural responses in the S1 encode the observed performance of behaving monkeys during vibrotactile discrimination tasks, and that the electrical microstimulation of the same S1 areas can substitute for the direct stimulation of the corresponding Meissner's corpuscles located at the finger tips and sensitive to frequencies (Ͻ50 Hz) subjectively perceived as a flutter (2).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, rabbits acquiring an associative learning using a trace-conditioning paradigm are unable to differentiate between the peripheral or central presentation of the same CS, i.e., their subjective experience was similar for both stimuli (1). These results also suggest that a similar sensory percept is evoked when animals are stimulated in the S1 area for vibrissae as when stimulated directly on the whisker pad (4,5). In this regard, it has been convincingly shown that neural responses in the S1 encode the observed performance of behaving monkeys during vibrotactile discrimination tasks, and that the electrical microstimulation of the same S1 areas can substitute for the direct stimulation of the corresponding Meissner's corpuscles located at the finger tips and sensitive to frequencies (Ͻ50 Hz) subjectively perceived as a flutter (2).…”
Section: Discussionsupporting
confidence: 56%
“…Thus, the neural activities recorded at the different S1 areas seem to correlate with sensory events (3). Accepting that centrally evoked sensory percepts could be similar to those evoked by peripheral stimuli (4,5), it can be hypothesized that the electrical microstimulation of selected S1 sites can substitute for peripheral skin receptor activation during the acquisition of an associative task, such as the classical conditioning of eyelid responses.…”
mentioning
confidence: 99%
“…medial premotor cortex ͉ monkeys ͉ sensory discrimination ͉ working memory S tudies in behaving monkeys that combine psychophysical and neurophysiological experiments have provided new insights into how a neural representation of a sensory stimulus relates to perception (1)(2)(3)(4)(5)(6)(7)(8), memory (9)(10)(11)(12), and decision making (13)(14)(15)(16)(17)(18)(19). In particular, there has been important progress regarding the neural codes associated with these cognitive functions in the visual and somatic modality (20,21).…”
mentioning
confidence: 99%
“…Although artificial cortical microstimulation can be perceptually indistinguishable from natural stimulation 15 , this need not always be the case; our results do not reveal the conditions under which such fine temporal differences are important for the readout of acoustically-evoked (i.e. natural) stimuli.…”
mentioning
confidence: 53%